History of The Umayyad Caliphate in Andalusia: A historical study of its diplomatic relations with the European Kingdoms / Isam Milaoud - Isam , Milaoud (2020)
This study discusses the Umayyad caliphate in Andalusia and its diplomatic relationship with the kingdoms of Europe during the fourth century AH, tenth century AD. It is considered one of the most flourishing centuries of Islamic Arab rule in Andalusia. At that time, Europe was in its dark ages. The great Western countries sought to reconcile Cordoba and come close to its caliphs. The following research question is used to investigate the problem under this study: What is the nature of Umayyad caliphate in Andalusia and its relationship with the kings of Europe? The present study aims to track the history of the Umayyad diplomatic relationship with the kings of Europe from the start of the caliphate until its end. It also highlights the characteristics of this relationship which reached its pinnacle during the era of Abd-Ar-Rahman Ill. Besides, it goals to identify the effective factors exchanged in the social, cultural, scientific and economic relationships between the Islamic Andalusia and the Christian Europe. The research methodology adopted here is the descriptive approach which meets the nature of this study; in addition, the historical approach is used as a supporting approach. The two approaches are adapted to fit in the social sciences research. The findings establish that the local opposition of the caliphate in Andalusia allied with foreign powers which in turn negatively impact on the relationship between the Andalusia and the kings of Europe. The conflict between the Islamic Andalusia and the Christian Europe started to gradually take an ideological religious form. The conflict ended by the end of one conflict party. The kings of Europe successfully reunited and ended the Islamic caliphate in Andalusia. The researcher, therefore, recommend further studies to be carried on this topic which both negatively and positively impact on the Islamic civilization.